Society of Uncertainty Part II. Aftermath and Collateral Damage of a Covid- 19 Pandemic (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This essay presents the scenario of uncertainty that Latin America is going through as a result of the emergence of the COVID19 pandemic, looking at some particularities that, although it is true, had already been worsening the impacts produced by the pandemic have contributed to the deepening of this deterioration. For this, it is necessary to take a tour of some aspects such as: the demographic composition in the region, the inadequate treatment that has been given to the information regarding the infections of the different ethnic groups with emphasis on the indigenous and Afro-descendant population, the habitability conditions and the relationship of this with the contagions of Covid19, the impact on the economy (GDP) and on the educational systems of the region. At another point in the essay, an analysis of the situation in Ecuador is made, taking several of the elements that are part of the generality (AL), but distinguishing itself with the electoral period that the South American country went through. Finally, the document calls on Latin America to face the health crisis in a more articulated way, and that this allows the continent to leave the scenario of uncertainty to embark on the path to certainty.
Keywords: Uncertainty; Pandemic; Society; Challenges; Economy